2005
DOI: 10.4103/0019-509x.15099
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and prognostic factors of early breast cancer at a major cancer center in North India

Abstract: BACKGROUND: Data on the clinical profile of early breast cancer (EBC) from India is scant. Due to differences in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
128
4
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(158 citation statements)
references
References 15 publications
(13 reference statements)
25
128
4
1
Order By: Relevance
“…Various Indian studies have shown receptor positivity as 43.9%, 50.5% and 53% [31,42,43]. In this study also 57% patients were estrogen receptor positive and 53% were positive for progesterone receptor.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Various Indian studies have shown receptor positivity as 43.9%, 50.5% and 53% [31,42,43]. In this study also 57% patients were estrogen receptor positive and 53% were positive for progesterone receptor.…”
Section: Discussionsupporting
confidence: 58%
“…In a study by Raina et al on EBC patients, 53.13% were node negative, 32.61% had 1-3 lymph nodes positive and 14.25% had >-4 lymph nodes positive [31]. In our study 51% patients were node negative, 32% had 1-3 lymph nodes positive and 17% had 4 or more lymph nodes positive for metastasis.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations